Migratory birds as the potential source for the transmission of Aspergillus and other fungus to Bangladesh - Mily Akter (Journal of Advanced Veterinary and Animal Research, 2020)
Objectives: Migratory birds play a major role in the transmission of pathogens globally, but still their role in the transmission of fungi in Bangladesh is not known. The present study was carried out for the isolation and molecular detection of fungi including Aspergillus from migratory birds traveling to Bangladesh. Materials and methods: A total of 50 fecal samples were collected from BaojaniBaor, Magura, and areas close to Jahangirnagar University, Savar. The isolation of fungus was based on culture on Potato Dextrose Agar (PDA), followed by staining, morphology, and molecular detection using polymerase chain reaction (PCR). Results: Among 50 samples, 40 showed positive for fungal growth on PDA, of which 30 yield only yeast-like colonies, five only molds, and five yielded both yeast and molds. The isolated molds produced various pigmented colonies, namely, black, whitish, grayish, olive green, and yellow. Among 10 molds, six were confirmed as fungi by PCR using genus-specific primers such as ITS1 and ITS4. Later, of these six fungi, five were confirmed as Aspergillus by PCR with primers such as ASAP1 and ASAP2 specific for Aspergillus genus. Therefore, the overall occurrence of Aspergillus was 10% (5/50). PCR specific for Aspergillus fumigatus and Aspergillus niger failed to produce specific PCR amplicon, suggesting that the isolated Aspergillus belongs to other groups. Conclusion: This is the first report describing the isolation and molecular detection of Aspergillus from fecal samples of migratory birds in Bangladesh. The present findings confirm that migratory birds are potential source for Aspergillus and other fungus in Bangladesh. [J Adv Vet Anim Res 2020; 7(2.000): 338-344]